Transcender les différends : une réaction possible aux situations de désaccord profond - David Zarefsky (Argumentation et Analyse du Discours, 2012)
Deep disagreement is a situation in which a conflict is so fundamental that there appears to be no underlying shared agreement by the arguers at any level. It is generally held that in such a case productive argument is not possible. Any claim the one party makes can be challenged by the other party in a potentially infinite regress, because there is no moment at which the interlocutor, by virtue of his or her prior commitments, is obligated to accept any standpoint. Overcoming deep disagreement requires transcending the impasse in the argument, seeing the controversy in a different light. This essay identifies four pairs of strategies that involve rhetorical moves to reset the disagreement and reshape the argument. In addition, two case studies are presented to illustrate these strategies, one a case of successful transcendence and the other a case of failure.